2012
DOI: 10.1021/la3026649
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Superhydrophilicity: A Kinetic Study of Time Dependent Photoinduced Contact Angle Changes on TiO2 Surfaces

Abstract: Transparent TiO(2) thin films were prepared on quartz substrates via a reverse micelle, sol-gel, spin-coating technique. The time dependence of the TiO(2) film photoinduced superhydrophilicity (PISH) was measured by goniometric observation of the contact angle, θ, of sessile water drops at the film surfaces. In these measurements, the TiO(2) substrate was illuminated by 315 nm light and drops were sequentially applied at a range of illumination times. Using a model for the wetting of heterogeneous surfaces der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
(93 reference statements)
1
17
0
Order By: Relevance
“…Within the framework of our experimental conditions, we determined a contact angle of 691 AE 41 on bare gold in accordance with a previous study, 85 521 AE 61 on titanium dioxide anatase layer, and 431 AE 41 on silicon wafer. If titanium dioxide was known to be highly hydrophilic, the value we have determined was actually coherent to the values reported in the literature 86 for a non-model surface that contains environmental impurities. These data have indicated that the gold surfaces, as prepared in these experiments, were the most hydrophobic samples and silicon wafers were the most hydrophilic.…”
Section: Effect Of Surface Type On Sophorolipid Assemblysupporting
confidence: 86%
“…Within the framework of our experimental conditions, we determined a contact angle of 691 AE 41 on bare gold in accordance with a previous study, 85 521 AE 61 on titanium dioxide anatase layer, and 431 AE 41 on silicon wafer. If titanium dioxide was known to be highly hydrophilic, the value we have determined was actually coherent to the values reported in the literature 86 for a non-model surface that contains environmental impurities. These data have indicated that the gold surfaces, as prepared in these experiments, were the most hydrophobic samples and silicon wafers were the most hydrophilic.…”
Section: Effect Of Surface Type On Sophorolipid Assemblysupporting
confidence: 86%
“…The self‐cleaning characteristics of semiconductors result not only from their strong oxidation power under irradiation, but also from the discovered phenomenon of the photoinduced superhydrophilicity inherent in the surface . Thus, one may consider the contribution of a self‐cleaning function combined with stability of the organized soft matter on a semiconductor for novel “intelligent” materials and nanoscale machineries.…”
Section: Photocatalytic Degradation Of Organic Species On Tio2mentioning
confidence: 99%
“…Photocatalysis is another facet of the problem (Fujishima et al, 2008) with higher ambition: in addition to producing solar fuels (typically hydrogen), one gains storage capability, a real Holy Grain since sunlight is not always available. Main efforts are focusing on water splitting (Walter et al, 2010; Valdes et al, 2012), an ideal process since energy production from hydrogen and oxygen only generates innocuous water as waste.…”
Section: Energy-related Topicsmentioning
confidence: 99%